2011
DOI: 10.14742/ajet.956
|View full text |Cite
|
Sign up to set email alerts
|

Data mining techniques for identifying students at risk of failing a computer proficiency test required for graduation

Abstract: <blockquote>Enabling undergraduate students to develop basic computing skills is an important issue in higher education. As a result, some universities have developed computer proficiency tests, which aim to assess students' computer literacy. Generally, students are required to pass such tests in order to prove that they have a certain level of computer literacy for successful graduation. This paper applies data mining techniques to make predictions about students who are going to take the computer prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…That is, these types of models incorporated, for instance, high school GPA, socio-economic status (SES), and scholastic aptitude test (SAT) scores in an algorithm to forecast student success or retention at a designated future time -such as at the end of a course in the first year of university (e.g. Agnihotri & Ott, 2014;Cochran, Campbell, Baker, & Leeds, 2013;Dekker, Pechenizkiy, & Vleeschouwers, 2009;Green, Plant, & Chan, 2016;Guruler, Istanbullu, & Karahasan, 2010;Harrak, Bouchet, Luengo, & Gillois, 2018;Kotsiantis, Pierrakeas, & Pintelas, 2003;Morris, Wu, & Finnegan, 2007;Tsai, Tsai, Hung, & Hwang, 2011;Yasmin, 2013;Yukselturk, Ozekes, & Türel, 2014). Traditional LA models thus included a relatively simple combination of student characteristics at one time-point to predict later academic performance (Williams, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…That is, these types of models incorporated, for instance, high school GPA, socio-economic status (SES), and scholastic aptitude test (SAT) scores in an algorithm to forecast student success or retention at a designated future time -such as at the end of a course in the first year of university (e.g. Agnihotri & Ott, 2014;Cochran, Campbell, Baker, & Leeds, 2013;Dekker, Pechenizkiy, & Vleeschouwers, 2009;Green, Plant, & Chan, 2016;Guruler, Istanbullu, & Karahasan, 2010;Harrak, Bouchet, Luengo, & Gillois, 2018;Kotsiantis, Pierrakeas, & Pintelas, 2003;Morris, Wu, & Finnegan, 2007;Tsai, Tsai, Hung, & Hwang, 2011;Yasmin, 2013;Yukselturk, Ozekes, & Türel, 2014). Traditional LA models thus included a relatively simple combination of student characteristics at one time-point to predict later academic performance (Williams, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that students' culture or ethnicity is one of the main factors affecting students' performance. Tsai et al [17] applied the K-means algorithm, unsupervised neural networks, and the C5.0 decision-tree algorithm at the National University in Taiwan to cluster and predict the undergraduate students. The purpose of the study was to develop an earlywarning system to identify the students who might fail one of the graduation requirement tests, the computer proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Xu and Yang (2016) use data involving learner activities such as video play activity and course forum activity from MOOCs on Coursera to predict student motivation and whether they will obtain a certification, using SVMs. Tsai et al (2011) evaluate the ability of various clustering techniques to derive decision trees to assess students’ computer literacy. Lopez et al (2012) analyse student participation in Moodle forums, including variables such as number of messages sent, number of messages read on the forum, time spent on the forum and degree centrality of the student, to estimate the final mark.…”
Section: Related Workmentioning
confidence: 99%